PEMANFAATAN DAUN Theprosia vogelii DALAM PENGENDALIAN HAMA Sitophilus zeamays (Coleoptera : Curculionidae) - Yustina Maria Silvia Wonga Puu (Agriculture Faculty of Flores University, 2020)
Sitophilus zeamays (Coleoptera: Curculionidae) is one of the pests that damage the corn kernels in storage so that it is damaged into corn powder. Control efforts that can be done is to use plant-based insecticides from Theprosia vogelii plants that contain rotenoid compounds so that they can cause pest mortality. The purpose of this study was to determine the effectiveness of Theprosia vogelli leaves in controlling Sitophilus zeamays in storage. The study was conducted at the Laboratory of the Faculty of Agriculture, University of Flores. The design used was a Completely Randomized Design (CRD) consisting of 5 treatments namely T0 = 0 gram (control), T1 (4 gram T. vogelii leaf powder), T2 (8 gram T. vogelii leaf powder), T3 (12 grams T. vogelii leaf powder) and T4 (16 grams of T. vogelii leaf powder). The observation variable was the mortality of the Sitophilus zeamays pest. The results showed that a dose of 16 grams of T. vogelii leaf powder caused a mortality of S. zeamays of 96.67%.